STATE FINANCIAL SUPPORT OF AGROINDUSTRIAL COMPLEX IN THE REPUBLIC OF KAZAKHSTAN - Sh.Sh. Ramazanova; N.K. Kuchukova; L.V. Legostaeva; Yu.V. Foo (Academic Journal of Physical and Chemical Sciences, 2019)
The authors described the importance of state financial support for the agro-industrial complex in accordance with the example of foreign countries leading in the field of agriculture. The modern world is set for economic integration, namely, in the context of globalization, increased competition, instability of consumer demand, the organizations of the Kazakhstani agro-industrial complex need to use modern development strategies and ideas and ensure financial and economic stability and reduce commercial risks.Management based on the strategy of diversification of production is important because the process of diversification is innovative, leading to the use of a new type of systemic technology and technology, new organization of labor and production with the support of the state.